A Formula for Calculating the Velocities of Fragments from Velocity Enhanced Warhead. Issue 2 (25th October 2012) - Wang, Mafa; Lu, Fangyun; Li, Xiangyu; Cao, Lei
Abstract A formula to predict the radial distribution of the fragment velocities of the Velocity Enhanced Warhead (VEW) is proposed. Not only the maximum velocity gains, but also the velocity gains with azimuth angle can be calculated using this formula. Its predictions are in good agreement with the experimental data from the previous literatures. This formula applies a correctional function in consideration of the directivity and initiation characteristics of the warhead fragments. The correlation between the coefficient k in the correctional function and the warhead property in terms of the ratio β of charge mass to metal casing mass is discussed. The fragment energy distribution can also be obtained from the formula and the results show that when β is equal to 1.0, half of the fragment energy is concentrated within the range of 63° in the target direction.